산화스트레스가 유도된 HepG2 세포에서 Eriodictyol의 항산화 효과 - 주태우(Tae-Woo Joo); 홍성현(Sung-Hyun Hong); 박선영(Sun-Young Park); 김거유(Gur-Yoo Kim); 주진우(Jin-Woo Jhoo) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2016)
This study was conducted to investigate the antioxidant and hepatoprotective effects of eriodictyol compound against hydrogen peroxide-induced oxidative stress in HepG2 cells by measuring expression levels of antioxidant enzymes, liver function index enzyme activities, and inhibitory effects against reactive oxygen species (ROS) production. HepG2 cell viability was assessed using 3-(4,5-dimethyl thiazole-2-yl)-2,5-diphenyl tetrazolium bromide assay. In the concentration range of $10{\sim}50μg/mL$, eriodictyol displayed over 98% cell viability in HepG2 cells. The effects of increased gene expression on hydrogen peroxide-induced oxidative stress were analyzed by monitoring antioxidant enzyme (superoxide dismutase, SOD; catalase, CAT; glutathione peroxidase, GPx) gene expression levels using real-time PCR. Eriodictyol compound significantly increased gene expression levels of SOD, CAT, and GPx in a dose-dependent manner ($10{\sim}50μg/mL$). Hepatoprotective effects against hydrogen peroxide-induced oxidative stress were analyzed by monitoring glutamic oxaloacetic transaminase (GOT), lactate dehydrogenase (LDH), and gamma-glutamyl transferase (GGT) activities in HepG2 cell culture medium using a biochemistry analyzer. Eriodictyol compound significantly reduced GOT, LDH, and GGT activities in a dose-dependent manner in HepG2 cells. ROS level in HepG2 cells was analyzed by 2',7'-dichlorofluorescein fluorescence diacetate assay, and eriodictyol compound effectively reduced the intracellular ROS level in HepG2 cells. The results reveal that eriodictyol compound can be useful for development of effective antioxidant and hepatoprotective agents. 본 연구는 싸리나무 잎에서 분리한 flavonoid 화합물인 eriodictyol의 항산화 활성을 평가하기 위해 hydrogen peroxide로 산화적 스트레스를 유도한 HepG2 세포에서 eriodictyol 화합물의 처리가 SOD-1, SOD-2, CAT 및 GPx의 유전자 발현에 미치는 영향을 분석하였으며, 또한 간 기능 지표효소인 GOT, LDH 및 GGT 활성을 분석하였다. 그리고 세포 내 활성산소종 생성 억제 효능을 분석하기 위하여 DCFH-DA assay를 실시하여 eriodictyol 화합물의 기능성 소재로서의 가능성을 알아보고자 본 실험을 하였다. Eriodictyol 화합물의 세포독성을 확인하기 위하여 HepG2 세포주를 이용하여 실시한 결과 eriodictyol 화합물을 $10{\sim}50μg/mL$의 농도로 처리한 모든 실험군에서 약 98% 이상의 세포생존율을 나타내었다. 항산화 효소 유전자 발현량을 통한 산화스트레스 억제 효과를 분석하기 위하여 HepG2 세포주에 hydrogen peroxide를 처리하여 산화스트레스가 증가시킨 조건에서 eriodictyol 화합물을 처리하여 SOD-1, SOD-2, CAT 및 GPx 발현량을 분석한 결과 eriodictyol 화합물의 처리 농도가 증가할수록 hydrogen peroxide 처리에 의해 감소한 SOD-1, SOD-2, CAT 및 GPx 발현량이 유의적으로 증가하는 것을 확인할 수 있었다. 간 기능 지표효소 활성을 측정하기 위해 GOT, LDH 및 GGT 활성을 분석한 결과 hydrogen peroxide로 단독 처리한 대조군과 eriodictyol 화합물을 처리한 군을 비교하였을 때 eriodictyol 화합물을 처리한 군에서 hydrogen peroxide 처리에 의해 증가한 GOT, LDH 및 GGT 활성이 유의적으로 감소하였다. HepG2 세포주에 eriodictyol 화합물을 처리하여 세포 내 활성산소종 생성에 미치는 영향을 DCFH-DA assay로 확인한 결과 eriodictyol 화합물의 농도가 증가함에 따라 세포내 활성산소종의 생성을 억제하는 것을 확인할 수 있었다. 따라서 본 실험을 통하여 eriodictyol 화합물은 산화적 스트레스로부터 항산화 효소 활성을 증가시키며, 활성산소종의 생성을 억제하는 효과를 확인할 수 있었다. 또한 간 기능 지표효소의 활성을 감소시켜 세포 보호 효과를 나타내어 항산화 활성 및 세포 보호 효과를 나타내는 기능성 소재로써 이용 가능성이 높을 것으로 판단되며, 후속연구를 통해 싸리나무 유래 eriodictyol 화합물의 세포 내 항산화 단백질 발현에 미치는 영향 및 동물실험을 통한 항산화 효과를 검증하는 것이 필요할 것으로 생각된다.